A Review on Virtual Reality and its Impact on Mankind - Kamde, Vikas; Patel, Rakesh; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
This report provides a short survey of the field of virtual reality, highlighting application domains, technological requirements, and currently available solutions. Virtual Reality (VR), sometimes called Virtual Environments (VE) has drawn much attention in the last few years. Extensive media coverage causes this interest to grow rapidly. Very few, people, however, really know what VR is, what its basic principles and its open problems are. In this paper a historical overview of virtual reality is presented, basic terminology and classes, of VR systems are listed, followed by applications of this technology in science, work, and entertainment areas. An insightful study of typical VR systems is done.